Perkembangan Aspek Fisik Pada Kawasan Sentra Produksi (KSP) Padi (Studi Kasus Kecamatan Ampek Angkek dan Kamang Magek, Kabupaten Agam) - Fastabiqul Khairad; Melinda Noer; Mahdi (Universitas Medan Area, 2023)
West Sumatera province government enhancement the growth of rice production through developing rice production centres. The centre is purpose to reduce cost and enhance efficiency that ultimately increases local economic growth. Kec. Ampek Angkek is a rice production centre in Agam district. In this case study, we explain the progress of centre development that set in 2013 of the physical aspect inside and outside production centre. The research method used is a qualitative descriptive with a case study approach. The condition of the development of physical aspect use a case to provide a detailed description of the development of the production centre. The result showed that there were similar developments for each aspect.